Implementation of One Sheet Learning Plan in Physics and Health Education Study in Smp Sub Rayon 06 Semarang Academic Year 2020/2021 - Ma'muroh, Ma'muroh; Rumini, Rumini; Soegiyanto, Soegiyanto (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
This study aims to analyze the various problems that arise as a result of curriculum changes, especially in the preparation of the Learning Implementation Plan. The Learning Implementation Plan in Permendikbud No. 22/2016 to the Minister of Education and Culture Circular No. 14 of 2019. Thus the focus of this research is 1) the response of sports and health physical education teachers to the implementation of the One-sheet Learning Implementation Plan for the Minister of Education and Culture 2019; 2) the effectiveness of the implementation of the one sheet of the 2019 Mendikbud's Learning Implementation Plan; 3) review of the one-sheet Learning Implementation Plan.This research took place at the Sub District 06 Junior High School in Semarang City with the research subjects were 12 physical education teachers. The main instruments of this research were 1) observation guide; 2) a questionnaire to get the respondent's opinion regarding the one sheet Learning Implementation Plan; 3) interviews to reveal respondents' opinions about curriculum changes regarding Permendikbud No. 22 of 2016 to the Minister of Education and Culture Circular No. 14 of 2019. The data collected through the use of these instruments are analyzed qualitatively with the main procedures: data collection, data reduction, data presentation, conclusions, and triangulation.The final result of this research is that the curriculum changes related to the preparation of the Learning Implementation Plan change from Permendikbud No. 22 of 2016 to the Circular of the Minister of Education and Culture No. 14 of 2019 which gives a good response to physical education teachers because, in addition to making it easier for teachers to design Learning Implementation Plans, these changes are also more effective, efficient and more learner-oriented.